Strategi Kebijakan dalam Mendukung Pengembangan UMKM di Kota Cilegon - Hana Septiana (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting regional economic growth, job creation, and equitable distribution of community welfare. In Cilegon City, MSMEs are growing rapidly in various sectors, but still face a number of fundamental challenges. The main problems faced include limited access to capital, low utilization of digital technology in business activities, limited managerial capacity, and less than optimal regulatory support oriented towards strengthening MSMEs. These conditions cause the competitiveness of MSMEs to be relatively weak compared to the large business sector, so that their contribution to the Gross Regional Domestic Product (GRDP) of Cilegon City is not optimal. This study aims to analyze policy strategies that can support the development of MSMEs in Cilegon City through a descriptive qualitative approach. The method used is a literature study and policy analysis by examining regulations, local government policies, and relevant previous research results. The analysis results show that there are several strategies that can be implemented, including: strengthening regulations and policies that favor MSMEs, expanding access to financing through collaboration with financial and banking institutions, developing human resource capacity through entrepreneurship and business management training, utilizing digital technology to expand market access, and building synergies between local governments, the private sector, and other supporting institutions. The implementation of these strategies is expected to increase the competitiveness of MSMEs, expand marketing networks, and encourage MSMEs to be more adaptive to technological developments and market needs. Thus, MSMEs in Cilegon City can make a more significant contribution to regional economic growth, create new jobs, and support sustainable economic development.